An indirect boundary element method for analysis of 3D thermoelastic problem with cracks. (June 2020) - Shen, Baotang; Shi, Jingyu
Abstract: In this paper, we first consider a combined boundary element method for numerical simulation of effect of temperature change on deformation due to time-varying heat conditions. The numerical simulation uses combination of an indirect boundary element method (IBEM) for temperature field and displacement discontinuity method (DDM) for displacement and stress fields. Time-varying fictitious heat source is employed in the IBEM and is approximated with a series of fictious heat sources with constant strengths that are applied incrementally at different times. Mathematically, the smooth-varying strength function of fictitious heat source is approximated with a stepwise function. The solution schemes previously developed for fictitious heat sources with constant strength are used for each increment. The combined scheme is used to compare the thermal effects caused by constant temperature and time-varying temperature on surface of a spherical cavity in an infinite body. The approximation scheme is verified with analytical solution when the temperature on the spherical cavity surface varies linearly with time. Then thermal fields around a conceptual thermal energy storage tank is simulated. Finally, the effects of temperature change in cracks connected to a vertical borehole on the propagation pattern of the cracks are investigated with the numerical scheme. It is found that cold temperature on the crack surfaces could help to reduce curvature of crack surfaces when multiple cracks are used, compared with fluid flow driven growth.